Tenofovir Alafenamide to Prevent Perinatal Hepatitis B Transmission: A Multicenter, Prospective, Observational Study. (4th January 2021) - Zeng, Qing-Lei; Yu, Zu-Jiang; Ji, Fanpu; Li, Guang-Ming; Zhang, Guo-Fan; Xu, Jiang-Hai; Chen, Zhi-Min; Cui, Guang-Lin; Li, Wei; Zhang, Da-Wei; Li, Juan; Lv, Jun; et al.
Abstract: Background: Few safety and effectiveness results have been published regarding the administration of tenofovir alafenamide fumarate (TAF) during pregnancy for the prevention of mother-to-child transmission (MTCT) of hepatitis B virus (HBV). Methods: In this multicenter prospective observational study, pregnant women with HBV DNA levels higher than 200 000 IU/mL who received TAF or tenofovir disoproxil fumarate (TDF) from gestational weeks 24–35 to delivery were 1:1 enrolled and followed until postpartum month 6. Infants received immunoprophylaxis. The primary endpoint was the safety of mothers and infants. The secondary endpoint was the hepatitis B surface antigen (HBsAg)-positive rate at 7 months for infants. Results: In total, 116 and 116 mothers were enrolled, and 117 and 116 infants were born, in the TAF and TDF groups, respectively. TAF was well tolerated during a mean treatment duration of 11.0 weeks. The most common maternal adverse event was nausea (19.0%). One (0.9%), 3 (2.6%), and 9 (7.8%) mothers had abnormal alanine aminotransferase levels at delivery and at postpartum months 3 and 6, respectively. The TDF group had safety profiles that were comparable to those of the TAF group. No infants had birth defects in either group. The infants' physical and neurological development at birth and at 7 months in the TAF group were comparable with those in the TDF group. The HBsAg positive rate was 0% at 7 months in all 233 infants. Conclusions: Antiviral prophylaxis with TAF was determined to be generally safe for both mothers and infants and reduced the MTCT rate to 0%. Abstract : Rare clinical data are available regarding tenofovir alafenamide fumarate (TAF) treatment during pregnancy. This multicenter, prospective, TDF-controlled, observational study demonstrated that TAF was safe for highly viremic pregnant women and their infants and reduced the mother-to-child transmission rate of hepatitis B virus (HBV) to 0%.